2023
DOI: 10.1002/adfm.202305650
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Radiation Thermal Protection Coating Based on Lamellar Porous Ca‐Cr co‐Doped Y3NbO7 Ceramic

Abstract: Dissipation of heat efficiently from a hot object via radiation while minimizing the inward heat conduction is the key requirement of radiation thermal protection. In this study, a Ca‐Cr co‐doped Y3NbO7 coating with lamellar porous structure is fabricated, which shows an ultra‐low thermal conductivity (<0.7 W m−1 K−1) and near‐unity emissivity (>0.9) across a broad wavelength range of ≈1–24 µm. This record high emissivity to thermal conductivity ratio (≈1.3) is experimentally and theoretically revealed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In Figure i, it can be observed that eight silica-oxygen tetrahedral coangled tops combine to form an octahedral ring when viewed perpendicular to the a -axis, and these octahedral rings possess a diameter ranging from 0.6 to 0.7 nm, while calcium ions are located at the edges of these octahedral rings. The stacking of eight-membered rings results in the formation of extensive cavity channels, resembling the structure of cordierite. , This distinctive architecture demonstrates enhanced material emissivity attributed to its nondense cavities that amplify molecular vibration and lattice resonance, , thereby leading to increased dipole moments and improved infrared emissive properties. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure i, it can be observed that eight silica-oxygen tetrahedral coangled tops combine to form an octahedral ring when viewed perpendicular to the a -axis, and these octahedral rings possess a diameter ranging from 0.6 to 0.7 nm, while calcium ions are located at the edges of these octahedral rings. The stacking of eight-membered rings results in the formation of extensive cavity channels, resembling the structure of cordierite. , This distinctive architecture demonstrates enhanced material emissivity attributed to its nondense cavities that amplify molecular vibration and lattice resonance, , thereby leading to increased dipole moments and improved infrared emissive properties. , …”
Section: Resultsmentioning
confidence: 99%
“…The stacking of eight-membered rings results in the formation of extensive cavity channels, resembling the structure of cordierite. 63,64 This distinctive architecture demonstrates enhanced material emissivity attributed to its nondense cavities that amplify molecular vibration and lattice resonance, 62,65 thereby leading to increased dipole moments and improved infrared emissive properties. 66,67 3.5.…”
Section: Porous Calcium Silicate Crystal Structure and Emission Mecha...mentioning
confidence: 99%
“…9 ), it is found that the micro-pyramid with w = 10 µm supports a strong electric dipole resonance, and weak magnetic dipole, electric quadrupole, and magnetic quadrupole resonances. Since the micro-pyramid is placed on the polydimethylsiloxane film, those resonance modes can couple to the polydimethylsiloxane film, which can cause strong forward scattering into the polydimethylsiloxane film 56 , 57 . Consequently, the reflection at the air-polydimethylsiloxane interface diminishes, more energy of the incident wave can be transmitted into the polydimethylsiloxane film, and the PMMM’ absorption in MIR range is thus enhanced based on Beer’s law.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the need for precise control over pyramid dimensions during fabrication is reduced, underscoring the material’s robustness and adaptability in manufacturing processes. To investigate this effect, we used the wave-optics module in COMSOL Multiphysics to study the electric field distribution around the micro-pyramid at its resonance wavelength 57 , as detailed in Supplementary Fig. 9 .…”
Section: Resultsmentioning
confidence: 99%
“…12 YSZ exhibits notable chemical and mechanical stability but is susceptible to degradation under extended high-temperature conditions due to phase transitions. 13–16 Hattori et al have previously investigated the deterioration mechanism of YSZ electrolytes due to the cubic-to-tetragonal phase transition, emphasizing its long-term thermal stability at high temperatures (1000 °C) under open circuit voltage. 17 Because SOECs operate under high temperatures and voltages, it is imperative to investigate the electrolyte's resistance to thermal and electrical degradation.…”
Section: Introductionmentioning
confidence: 99%